PSXVI-36 Factors influencing blood urea nitrogen concentration in Angus cattle. - Speidel, S (J Anim Sci, 2018)
Excess nitrogen excretion is viewed as a worldwide environmental problem, and blood urea nitrogen (BUN; mg/dl) has been shown to be a predictor of nitrogen excretion in cattle. As a result, the objective of this study was to identify factors influencing BUN in a cohort of Angus cattle. Steers (n = 98) were born between February and June of 2016 and entered Colorado State University’s Feed Intake Unit (FIU) in May 2017 at an average age of 394.6 ± 21.0 d. While in the FIU, steers were fed a growing diet consisting primarily of corn silage and alfalfa hay. Animals were subjected to a 20 d warm-up period and a 54 d individual feed intake test period. Blood samples were collected on d 50 of the test. A generalized linear regression model was used to determine factors important in the determination of BUN concentrations of individual animals. Factors considered were sire, BUN assay date, age, initial test weight, birth weight, weaning weight, average daily gain, dry matter intake, residual feed intake, pulmonary arterial pressure, ultrasound ribeye area, ultrasound back fat, ultrasound percent intramuscular fat, and feedlot pen. Sire (P < 0.0005; partial r(2) = 0.47), BUN assay date (P < 0.00005; partial r(2) = 0.46) and age (P < 0.005; partial r(2) = 0.18) were all important sources of variation of BUN concentration levels. Sire and assay date explained the largest proportion of variability in BUN concentration as evidenced by their partial r(2) values. Sample process date and age are factors in which cattle producers would have little control in mitigating BUN concentrations, but that could be adjusted for with proper data recording. Differences amongst sires, however, indicate genetic differences may be exploited to reduce BUN concentrations.